Analysis of Differentiated Learning in Indonesian Language Subjects for Elementary School Students - Desfita Muliadi; Sindi Winarsih; Nurul Hasanah; Aliya Ramadani (CV. Edujavare Publishing, 2026)
The diversity of learning readiness, interests, and learning styles of elementary school students requires teachers to implement learning that is no longer uniform, especially since the Independent Curriculum requires student-centered learning through a differentiated approach, while Indonesian language learning has tended to be teacher-centered. This study aims to analyze the implementation of differentiated learning in Indonesian language subjects in elementary schools, the forms of content, process, and product differentiation applied, and the obstacles faced by teachers in its implementation. The method used is a library study (library research) with a qualitative approach and content analysis techniques on six articles from accredited national journals published in 2020–2026. The results of the study indicate that all articles report the positive impact of differentiated learning on student activity, motivation, and learning outcomes; process differentiation is most often applied compared to content and product, with diagnostic assessment as a key instrument for mapping student needs; and three main obstacles that are consistently reported are time constraints, large student numbers in one class, and teachers' lack of understanding of student learning styles. It can be concluded that differentiated learning effectively improves the quality of Indonesian language learning in elementary schools, but its success depends on systemic support in the form of continuous teacher training and adjustment of the student ratio per class, so that future research is recommended to use a quantitative design to measure the magnitude of its impact measurably.